Gas black produced from rubber-derived pyrolysis oil
The production of gas black in the gas black reactor by thermal oxidation and decomposition of rubber-derived tar is solved, and the problems of limited fossil raw material resources and environmental pollution are achieved, and efficient and environmentally friendly gas black production is achieved, which meets the requirements of the circular economy.
Patent Information
- Application Number
- JP2024563503
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-04-29
- Filing Date
- 2023-04-25
- Publication Date
- 2025-05-02
AI Technical Summary
The use of fossil raw materials in the existing gas black production process leads to limited resources and environmental pollution. When these raw materials are replaced with recyclable materials, the gas black reactor is prone to blockage and it is difficult to achieve efficient production.
By thermal oxidation and decomposition, rubber-derived tar is used as raw material to produce gas black in the gas black reactor. The rubber-derived tar contains tire-derived tar. By controlling the composition and reaction conditions of the tar, the stability of the production process and the quality of the product are ensured.
The use of recyclable materials to produce gas black is realized, which avoids excessive consumption of fossil raw materials and environmental pollution, and improves the stability of the production process and the performance of the product, which meets the requirements of the circular economy.
Smart Images

Figure 2025514276000001 
Figure 2025514276000002 
Figure 2025514276000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing carbon black, and to carbon black obtained by such a method, as well as uses of such carbon black. The present invention further relates to compositions comprising such carbon black, as well as uses of such compositions and articles prepared from such compositions. [Background technology]
[0002] Carbon black produced by the gas black process offers beneficial properties in many applications, for example as a pigment.
[0003] However, gas black is traditionally produced using fossil raw materials such as coal and crude oil. Fossil raw materials are limited and are being depleted at a fast rate. Moreover, fossil raw materials are primarily harmful to the environment due to the high environmental impact of their extraction and transportation. For example, oil spills have occurred in the past, leading to the contamination of water bodies and the death of aquatic animals, including those living offshore. Furthermore, the combustion of fossil raw materials, and thus the production of carbon dioxide, is known to be one of the main causative factors of global warming. The reasons for pursuing alternatives to fossil raw materials are the unstable prices and the dependency on politically unstable regions for the transportation of fossil raw materials.
[0004] It is desirable to avoid the disadvantages that come from the use of fossil raw materials. Recyclable materials are more environmentally friendly as raw materials for the production of carbon black. The use of recyclable raw materials contributes to the conservation of limited fossil resources and creates opportunities for the realization of a circular economy. However, replacing fossil raw materials with other raw materials in the gas black process is difficult because gas black reactors are prone to clogging of the feed lines and burners, requiring shutdown and disassembly of the equipment for cleaning.
[0005] Depending on the various applications, it is desirable for carbon black materials produced from recyclable raw materials to exhibit certain properties comparable to known carbon blacks.
[0006] It is therefore an object of the present invention to provide a method for producing carbon black that creates opportunities for the realization of a circular economy and provides carbon black with properties comparable to known, established carbon blacks. Summary of the Invention
[0007] It has surprisingly been shown that this object can be achieved by the process and the carbon black obtained by this process as disclosed in the independent claims. Particular or preferred variants of the invention are set out in the dependent claims.
[0008] The following section summarizes certain aspects of the present invention.
[0009] A first aspect of the present invention relates to a process for producing carbon black by thermo-oxidative decomposition of a carbon black feedstock, wherein the carbon black feedstock comprises a rubber-derived pyrolysis oil and the production of carbon black is carried out in a gas black reactor.
[0010] A second aspect of the present invention relates to the method according to the first aspect, wherein the rubber-derived pyrolysis oil comprises tire-derived pyrolysis oil (TPO).
[0011] A third aspect of the present invention relates to a method according to the first or second aspect, wherein the rubber-derived pyrolysis oil comprises tire-derived pyrolysis oil (TPO).
[0012] A fourth aspect of the present invention relates to a method according to any one of the preceding aspects, wherein the rubber-derived pyrolysis oil is - a total carbon content in the range of 80.0 to 90.0% by mass, - a total amount of hydrogen in the range of 8.0 to 15.0% by mass, and - C / H atomic ratio in the range of 0.60 to 1.0, wherein the mass % is based on the total mass of the rubber-derived pyrolysis oil excluding moisture and ash, and the total carbon and total hydrogen are measured according to ASTM D5291C-21.
[0013] A fifth aspect of the present invention relates to a method according to any one of the preceding aspects, wherein the rubber-derived pyrolysis oil comprises: - a total carbon content in the range of 85.0 to 90.0% by mass, - a total amount of hydrogen in the range of 8.0 to 11.0% by mass, and - C / H atomic ratio in the range of 0.65 to 1.0, wherein the mass % is based on the total mass of the rubber-derived pyrolysis oil excluding moisture and ash, and the total carbon and total hydrogen are measured according to ASTM D5291C-21.
[0014] A sixth aspect of the present invention relates to a method according to any one of the preceding aspects, wherein the rubber-derived pyrolysis oil is - a total carbon content in the range of 86.0 to 90.0% by mass, - a total amount of hydrogen in the range of 8.5 to 10.5% by mass, and - C / H atomic ratio in the range of 0.70 to 0.90, wherein the mass % is based on the total mass of the rubber-derived pyrolysis oil excluding moisture and ash, and the total carbon and total hydrogen are measured according to ASTM D5291C-21.
[0015] A seventh aspect of the present invention relates to a method according to any one of the preceding aspects, wherein the rubber-derived pyrolysis oil comprises: - a total carbon content ranging from 87.0 to 90.0% by mass, - a total amount of hydrogen in the range of 9.0 to 10.0% by mass, and - C / H atomic ratio in the range of 0.70 to 0.85, wherein the mass % is based on the total mass of the rubber-derived pyrolysis oil excluding moisture and ash, and the total carbon and total hydrogen are measured according to ASTM D5291C-21.
[0016] An eighth aspect of the present invention relates to a method according to any one of the preceding aspects, wherein the rubber-derived pyrolysis oil comprises: - Maximum total nitrogen content of 1.00% by weight, and / or - maximum total sulfur content of 1.35% by weight; wherein the mass % is based on the total mass of the rubber-derived pyrolysis oil excluding moisture and ash, and the total nitrogen and total sulfur are measured according to ASTM D5291C-21.
[0017] A ninth aspect of the present invention relates to a method according to any one of the preceding aspects, wherein the rubber-derived pyrolysis oil comprises: - Maximum 0.80% total nitrogen by weight, and / or - maximum total sulfur content of 1.25% by weight; wherein the mass % is based on the total mass of the rubber-derived pyrolysis oil excluding moisture and ash, and the total nitrogen and total sulfur are measured according to ASTM D5291C-21.
[0018] A tenth aspect of the present invention relates to a method according to any one of the preceding aspects, wherein the rubber-derived pyrolysis oil comprises: - maximum total nitrogen content of 0.65% by weight, and / or - maximum total sulfur content of 1.20% by weight; wherein the mass % is based on the total mass of the rubber-derived pyrolysis oil excluding moisture and ash, and the total nitrogen and total sulfur are measured according to ASTM D5291C-21.
[0019] An eleventh aspect of the present invention relates to a method according to any one of the preceding aspects, wherein the rubber-derived pyrolysis oil comprises: - an ash content of less than 0.04 mass %, where mass % is based on the total mass of the rubber-derived pyrolysis oil and the ash content is measured according to ASTM D2415-20.
[0020] A twelfth aspect of the present invention relates to a method according to any one of the preceding aspects, wherein the rubber-derived pyrolysis oil comprises: - an ash content of less than 0.03% by weight, where the weight percent is based on the total weight of the rubber-derived pyrolysis oil and the ash content is measured according to ASTM D2415-20.
[0021] A thirteenth aspect of the present invention relates to a method according to any one of the preceding aspects, wherein the rubber-derived pyrolysis oil comprises: - a sieve residue of maximum 250 mg / kg, measured according to ASTM D4870-18 (25 μm mesh size), based on the total weight of rubber-derived pyrolysis oil.
[0022] A fourteenth aspect of the present invention relates to a method according to any one of the preceding aspects, wherein the rubber-derived pyrolysis oil comprises: - having a sieve residue of maximum 230 mg / kg, measured according to ASTM D4870-18 (25 μm mesh size), based on the total weight of rubber-derived pyrolysis oil.
[0023] A fifteenth aspect of the present invention is the method according to any one of the second to fourteenth aspects, wherein the tire-derived pyrolysis oil (TPO) is - a total carbon content in the range of 85.0 to 90.0% by mass, - a total amount of hydrogen in the range of 8.0 to 11.0% by mass, and - C / H atomic ratio in the range of 0.65 to 1.0, where weight percent is based on the total weight of the TPO excluding moisture and ash, and total carbon and total hydrogen are measured according to ASTM D5291C-21.
[0024] A sixteenth aspect of the present invention is the method according to any one of the second to fifteenth aspects, wherein the TPO is - a total carbon content in the range of 86.0 to 90.0% by mass, - a total amount of hydrogen in the range of 8.5 to 10.5% by mass, and - C / H atomic ratio in the range of 0.70 to 0.90, where weight percent is based on the total weight of the TPO excluding moisture and ash, and total carbon and total hydrogen are measured according to ASTM D5291C-21.
[0025] A seventeenth aspect of the present invention is a method according to any one of the second to sixteenth aspects, wherein the TPO is - a total carbon content ranging from 87.0 to 90.0% by mass, - a total amount of hydrogen in the range of 9.0 to 10.0% by mass, and - C / H atomic ratio in the range of 0.70 to 0.85, where weight percent is based on the total weight of the TPO excluding moisture and ash, and total carbon and total hydrogen are measured according to ASTM D5291C-21.
[0026] An 18th aspect of the present invention is a method according to any one of the 2nd to 17th aspects, wherein the TPO is - a total nitrogen content of 0.40 to 0.65% by weight, and / or - maximum total sulfur content of 1.35% by weight; where weight percent is based on the total weight of the TPO excluding moisture and ash, and total nitrogen and total sulfur are measured according to ASTM D5291C-21.
[0027] A nineteenth aspect of the present invention is a method according to any one of the second to eighteenth aspects, wherein the TPO is - a total nitrogen content of 0.45 to 0.65% by weight, and / or - maximum total sulfur content of 1.25% by weight; where weight percent is based on the total weight of the TPO excluding moisture and ash, and total nitrogen and total sulfur are measured according to ASTM D5291C-21.
[0028] A twentieth aspect of the present invention is a method according to any one of the second to nineteenth aspects, wherein the TPO is - 0.45 to 0.60% total nitrogen by weight, and / or - maximum total sulfur content of 1.20% by weight; where weight percent is based on the total weight of the TPO excluding moisture and ash, and total nitrogen and total sulfur are measured according to ASTM D5291C-21.
[0029] A twenty-first aspect of the present invention is a method according to any one of the second to twentieth aspects, wherein the TPO is - an ash content of less than 0.04 wt.%, where wt.% is based on the total weight of the TPO and the ash content is measured according to ASTM D2415-20.
[0030] A 22nd aspect of the present invention is a method according to any one of the 2nd to 21st aspects, wherein the TPO is - an ash content of less than 0.03 wt.%, where wt.% is based on the total weight of the TPO and the ash content is measured according to ASTM D2415-20.
[0031] A 23rd aspect of the present invention is a method according to any one of the 2nd to 22nd aspects, wherein the TPO is - a sieve residue of maximum 250 mg / kg, measured according to ASTM D4870-18 (25 μm mesh size), based on the total weight of the TPO.
[0032] A 24th aspect of the present invention is a method according to any one of the 2nd to 23rd aspects, wherein the TPO is - a sieve residue of maximum 230 mg / kg, based on the total weight of the TPO, measured according to ASTM D4870-18 (25 μm mesh size).
[0033] A twenty-fifth aspect of the present invention relates to the method according to any one of the preceding aspects, wherein the carbon black feedstock further comprises a conventional carbon black feedstock comprising coal tar distillate, a residual oil produced during catalytic cracking of petroleum fractions, a residual oil produced during the production of olefins by cracking naphtha or gas oil, or a mixture of any combination thereof, preferably a coal tar distillate.
[0034] A twenty-sixth aspect of the present invention relates to the method according to any one of the preceding aspects, wherein the carbon black feedstock comprises at least 10 wt.%, preferably at least 30 wt.%, more preferably at least 50 wt.%, even more preferably at least 70 wt.%, and most preferably at least 90 wt.%, of the rubber-derived pyrolysis oil, based on the total weight of the carbon black feedstock.
[0035] A twenty-seventh aspect of the present invention relates to the method of any one of the preceding aspects, wherein the carbon black feedstock consists of rubber-derived pyrolysis oil.
[0036] A twenty-eighth aspect of the present invention relates to the method of any one of the preceding aspects, wherein the rubber-derived pyrolysis oil comprises at least 10 wt.%, preferably at least 30 wt.%, more preferably at least 50 wt.%, even more preferably at least 70 wt.%, and most preferably at least 90 wt.% tire-derived pyrolysis oil (TPO), based on the total weight of the rubber-derived pyrolysis oil.
[0037] A twenty-ninth aspect of the present invention relates to a method according to any one of the preceding aspects, comprising vaporizing the carbon black raw material in a carrier gas stream, combusting the carrier gas stream loaded with the carbon black raw material in the presence of air in a burner to form carbon black, and terminating the carbon black formation.
[0038] A thirtieth aspect of the present invention relates to a carbon black obtained by a method according to any one of the preceding claims, wherein the carbon black is a gas black.
[0039] A thirty-first aspect of the present invention is the carbon black according to the thirtieth aspect, - relates to carbon blacks having an oil absorption number (OAN) of 110 mL / 100 g or more, where OAN is measured according to ASTM D2414-21.
[0040] A 32nd aspect of the present invention is the carbon black according to the 30th or 31st aspect, - a volatile content of 6% or more, where the volatile content (at 950°C) is determined according to DIN 53552:1977-09.
[0041] A thirty-third aspect of the present invention relates to the carbon black according to any one of the thirty to thirty-second aspects, wherein the carbon black has an OAN in the range of 110 to 180 mL / 100 g, preferably 115 to 165 mL / 100 g, wherein the OAN is measured according to ASTM D2414-21.
[0042] A thirty-fourth aspect of the present invention relates to the carbon black according to any one of the thirty-first to thirty-third aspects, wherein the carbon black has a volatile content in the range of 6% to 10%, wherein the volatile content (at 950° C.) is measured according to DIN 53552:1977-09.
[0043] In a 35th aspect of the present invention, the carbon black is 70 to 300 m 2 / g, preferably 70 to 270 m 2 / g, more preferably 80 to 250m 2 The carbon black according to any one of the 30th to 34th aspects, having an STSA in the range of 1 / g, wherein the STSA is measured according to ASTM D6556-19a.
[0044] In a 36th aspect of the present invention, carbon black is 80 to 350 m 2 / g, preferably 80 to 320 m 2 / g, more preferably 90 to 300m 2 / g, wherein the BET surface area is measured in accordance with ASTM D6556-19a.
[0045] A thirty-seventh aspect of the present invention relates to the carbon black according to any one of the thirty to thirty-sixth aspects, wherein the carbon black has a color strength in the range of 30 to 250%, preferably 50 to 160%, wherein the color strength is measured according to ASTM D3265-21.
[0046] A thirty-eighth aspect of the present invention relates to a carbon black according to any one of the thirty to thirty-seventh aspects, wherein the carbon black has a pMC (percent modern carbon) in the range of 1 to 65%, preferably 5 to 60%, more preferably 10 to 60%, even more preferably 15 to 55%, wherein pMC is measured according to ASTM D6866-20B method (AMS).
[0047] A thirty-ninth aspect of the present invention relates to the carbon black according to any one of the thirty to thirty-eighth aspects, wherein the carbon black is oxidized and / or functionalized.
[0048] A fortieth aspect of the present invention relates to the use of the carbon black according to any one of the thirtieth to thirty-ninth aspects as a reinforcing filler or additive, a UV stabilizer, a conductive carbon black or pigment, preferably as a pigment.
[0049] A forty-first aspect of the present invention relates to the use of a carbon black according to any of the thirtieth to thirty-ninth aspects in rubber and rubber mixtures, plastics, inks, such as printing inks, inkjet inks or other inks, toners, lacquers, coatings, paper, adhesives or in battery or black matrix applications, preferably in inks, lacquers and coatings.
[0050] A forty-second aspect of the present invention relates to a composition containing the carbon black according to any one of the thirtieth to thirty-ninth aspects.
[0051] A forty-third aspect of the present invention relates to the composition according to the forty-second aspect, wherein the composition is an ink composition, a coating composition or a lacquer composition.
[0052] A forty-fourth aspect of the present invention relates to an article prepared from the composition according to the forty-third aspect.
[0053] A forty-fifth aspect of the present invention relates to the article according to the forty-fourth aspect, which is a coated or pigmented or printed article. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0054] The present invention relates to a process for producing carbon black by thermo-oxidative decomposition of a carbon black feedstock. The carbon black feedstock of the present invention comprises a rubber-derived pyrolysis oil. The production of carbon black is carried out in a gas black reactor. The process of the present invention is therefore a gas black process.
[0055] As used herein, the term "carbon black" refers to a material that is substantially composed of, for example, more than 80% by weight, or more than 90% by weight, or more than 95% by weight, based on the total weight of carbon. The production of carbon black by the gas black process is well known in the art and is reviewed, for example, in J.-B. Donet et al., "Carbon Black: Science and Technology", 2nd Edition, Marcel Dekker Co., New York (1993), pp. 57-58; H. Felch, "Pigments", 1st Edition, Kurt R. Vinzenz Verlag, Hannover (1995), pp. 31-33; and "Ullmann's Encyclopedia of Chemical Engineering", 3rd Edition, Vol. 14 (1963), pp. 798-799; and in DE 845683 C, DE 504428 C, and US Patent Publication No. 3978019.
[0056] A conventional gas black reactor is shown on page 33 of H. Feltsch, "Pigments", 1st Edition, Kurt R. Vinzenz Verlag, Hannover (1995), and on page 799 of "Ullmann's Encyclopedia of Chemical Engineering", 3rd Edition, Vol. 14 (1963).
[0057] The process of the present invention can include vaporizing a carbon black feedstock in a carrier gas stream, combusting the carrier gas stream loaded with the carbon black feedstock in the presence of air in a burner to form carbon black, and terminating the carbon black formation.
[0058] The carbon black feedstock of the present invention can be heated in a vaporizer and the resulting gas carried to a burner by a carrier gas. The carrier gas stream can include hydrogen, oxygen, nitrogen, methane, natural gas, CO2, and mixtures thereof. The carrier gas is loaded with the vaporized carbon black feedstock and the m of the carrier gas can be used to heat the carbon black feedstock. 3 The gasification pipe may contain 400-2200 g of vaporized carbon black raw material per burner. The carrier gas may, for example, be passed directly or countercurrently over the carbon black raw material, or the carrier gas may be directed over stationary carbon black. Preferably, the carrier gas is heated to a suitable temperature, for example, a vaporization temperature of the carbon black raw material, such as a temperature in the range of 200-400°C. When delivering the mixture containing the carrier gas and the vaporized carbon black raw material to the burner, the temperature of the mixture of the carrier gas and the vaporized carbon black raw material may be within a range such that there is no accumulation or premature decomposition of the carbon black raw material in the pipe or burner. Preferably, the temperature up to the burner is maintained not to exceed 350-400°C.
[0059] The carrier gas loaded with the vaporized carbon black feedstock can be combusted in the presence of air in a burner to form carbon black. Carbon black formation is typically terminated by depositing the formed carbon black into a cooled device, such as a cylinder, a moving sledge, a pan apparatus, or the like. The deposition device can be water cooled.
[0060] In a conventional gas black reactor, the gas black burner and the deposition device, such as the deposition roller, are generally arranged jointly in a housing. The water-cooled deposition roller can have a diameter of 0.4-0.7 m and a length of 3-7 m, and typically rotates at 0.8-1.25 rpm. At the top of the housing, the exhaust gases can be sucked out and guided to a filter plant via a pipeline. The carrier gas generally enters through the open lower surface of the housing. In a conventional gas black reactor, individual cast iron burners can be arranged side by side, which generate a fan-shaped diffusion flame by means of a flat nozzle arranged perpendicular to the axis of the deposition roller. The burners are typically arranged on connections arranged in the jacket of the gas supply pipe. The gas supply pipe can be arranged below the cooling roller and parallel to its axis. The distance of the burner nozzle can be selected so that the flame burns towards the rotating roller and is thereby cooled.
[0061] As used herein, the term "rubber-derived pyrolysis oil" refers to the liquid fraction obtained from the pyrolysis of rubber articles. Rubber-derived pyrolysis oil typically contains a mixture of saturated and unsaturated hydrocarbons and may contain polar compounds containing sulfur, nitrogen and oxygen.
[0062] Pyrolysis of rubber articles generally involves heating the rubber article to a temperature of, for example, at least 300° C. in the absence of oxygen to volatilize and decompose the rubber article to produce oil, gas, and char. As used herein, the term "rubber article" refers to an article comprised of rubber, for example, an article comprised of at least 50% by weight of rubber based on the total weight of the rubber article. Examples of rubber articles include, but are not limited to, tires, conveyor belts, gaskets such as door gaskets, drive belts, floor mats, shoe soles, belts, cable sheaths, hoses, and the like. A preferred rubber article includes tires. The term "rubber" includes both natural and synthetic rubber, or mixtures thereof. Natural rubber can be obtained from rubber trees (Helvea brasiliensis), guairu, and dandelion. Synthetic rubbers can include styrene-butadiene rubbers, such as emulsion-styrene-butadiene rubber and solution-styrene-butadiene rubber, polybutadiene, polyisoprene, ethylene-propylene-diene rubber, ethylene-propylene rubber, butyl rubber, halogenated butyl rubber, chlorinated polyethylene, chlorosulfonated polyethylene, acrylonitrile-butadiene rubber, hydrogenated acrylonitrile-butadiene rubber, polychloroprene, acrylate rubber, ethylene-vinyl acetate rubber, ethylene-acrylic rubber, epichlorohydrin rubber, silicone rubber, fluorosilicone rubber, fluorocarbon rubber, or a mixture of any combination of the foregoing.
[0063] According to the present invention, the rubber-derived pyrolysis oil can include tire-derived pyrolysis oil (TPO). As used herein, the term "tire-derived pyrolysis oil" ("TPO") refers to a liquid fraction obtained in the pyrolysis of tires in the absence of oxygen. TPO generally contains a mixture of saturated and unsaturated hydrocarbons and can contain polar compounds including sulfur, nitrogen and oxygen. Typically, waste tires, also known as "used" tires (ELT), are used in pyrolysis to obtain TPO. As used herein, "waste tires" or "used tires" refers to tires that are not suitable for use in vehicles due to irreparable damage such as wear or punctures, for example, truck tires, passenger tires, off-road tires, aircraft tires, agricultural tires, and earthmover tires.
[0064] The pyrolysis method of rubber articles such as tires is well known in the art and involves heating tires in the absence of oxygen. Suitable processes for obtaining rubber-derived pyrolysis oil, especially TPO, include, but are not limited to, those described in US 2002 / 0072641 A1, US 2002 / 0072640 A1, US 2005 / 0101812 A1 and EP 2427533 A1.
[0065] The rubber-derived pyrolysis oil may comprise at least 5% by weight, for example at least 10% by weight, or at least 10% by weight, or at least 15% by weight, or at least 20% by weight, or at least 25% by weight, or at least 30% by weight, or at least 35% by weight, or at least 40% by weight, or at least 45% by weight, or at least 50% by weight, or at least 55% by weight, or at least 60% by weight, or at least 65% by weight, or at least 70% by weight, or at least 75% by weight, or at least 80% by weight, or at least 85% by weight, or at least 90% by weight, or at least 95% by weight, or at least 99% by weight of tire-derived pyrolysis oil (TPO), based on the total weight of the rubber-derived pyrolysis oil. According to the present invention, the rubber-derived pyrolysis oil may comprise at least 10% by weight, preferably at least 30% by weight, more preferably at least 50% by weight, even more preferably at least 70% by weight, and most preferably at least 90% by weight of TPO, based on the total weight of the rubber-derived pyrolysis oil. The rubber-derived pyrolysis oil of the present invention can consist of TPO.
[0066] A suitable example of a rubber-derived pyrolysis oil, particularly a TPO, is ThermoTireOil RR manufactured by Pyram Innovations (Germany), but is not limited thereto.
[0067] According to the present invention, the rubber-derived pyrolysis oil may have a flash point of at least 3°C, preferably at least 5°C, more preferably at least 50°C, and most preferably at least 65°C. As used herein, the term "flash point" refers to the minimum temperature at which volatile materials vaporize to form an ignitable mixture in air. Flash point may be measured according to ASTM D93D. The rubber-derived pyrolysis oil may be processed, for example, by distillation, such as fractional distillation at atmospheric pressure, thin film distillation, etc., to obtain a fraction with a higher flash point, such as at least 65°C.
[0068] According to the present invention, the rubber-derived pyrolysis oil can have a total carbon content of at least 80.0% by mass, for example at least 81.0% by mass, or at least 82.0% by mass, or at least 83.0% by mass, or at least 84.0% by mass, or at least 85.0% by mass, or at least 85.5% by mass, or at least 86.0% by mass, or at least 86.5% by mass, or at least 87.0% by mass, or at least 87.5% by mass, where the mass percentage is based on the total mass of the rubber-derived pyrolysis oil excluding moisture and ash. The rubber-derived pyrolysis oil can have a total carbon content of 90.0% by mass or less, for example, 89.5% by mass or less, or 89.0% by mass or less, where the mass percentage is based on the total mass of the rubber-derived pyrolysis oil excluding moisture and ash. The moisture content can be measured according to ASTM D4928-12R18, and the ash content can be measured according to ASTM D2415-20 (at 550°C). A person skilled in the art would understand that any range between any of the explicitly disclosed lower and upper limits is disclosed herein. Thus, the rubber-derived pyrolysis oil can have a total carbon content ranging from 80.0 to 90.0 mass%, preferably 85.0 to 90.0 mass%, more preferably 86.0 to 90.0 mass%, and most preferably 87.0 to 90.0 mass%, where mass% is based on the total mass of the rubber-derived pyrolysis oil excluding moisture and ash. The total carbon content is measured according to ASTM D5291C-21.
[0069] According to the present invention, the rubber-derived pyrolysis oil can have a total hydrogen content of at least 8.0 mass%, for example at least 8.5 mass%, or at least 9.0 mass%, or at least 9.5 mass%, where mass% is based on the total mass of the rubber-derived pyrolysis oil excluding moisture and ash. Moisture can be measured according to ASTM D4928-12R18, and ash can be measured according to ASTM D2415-20 (at 550°C). The rubber-derived pyrolysis oil can have a total hydrogen content of 15.0 mass% or less, for example, 14.0 mass% or less, or 13.0 mass% or less, or 12.0 mass% or less, or 11.0 mass% or less, or 10.5 mass% or less, or 10.0 mass% or less, where mass% is based on the total mass of the rubber-derived pyrolysis oil excluding moisture and ash. A person skilled in the art would understand that any range between any of the explicitly disclosed lower and upper limits is disclosed herein. Therefore, the rubber-derived pyrolysis oil may have a total hydrogen content in the range of 8.0 to 15.0 mass%, preferably 8.0 to 11.0 mass%, more preferably 8.5 to 10.5 mass%, and most preferably 9.0 to 10.0 mass%, where mass% is based on the total mass of the rubber-derived pyrolysis oil excluding moisture and ash. The total hydrogen content is measured according to ASTM D5291C-21.
[0070] According to the present invention, the rubber-derived pyrolysis oil can have a C / H atomic ratio of at least 0.60, such as at least 0.65, or at least 0.70, or at least 0.75. The rubber-derived pyrolysis oil can have a C / H atomic ratio of 1.0 or less, such as 0.95 or less, or 0.90 or less, or 0.85 or less, or 0.80 or less. A person skilled in the art will understand that any range between any of the explicitly disclosed lower and upper limits is disclosed herein. Thus, the rubber-derived pyrolysis oil can have a C / H atomic ratio in the range of 0.60 to 1.0, preferably 0.65 to 1.0, preferably 0.70 to 0.90, more preferably 0.70 to 0.85. The C / H atomic ratio is calculated from the total carbon and total hydrogen determined as described above according to ASTM D5291C-21.
[0071] Rubber-derived pyrolysis oil is a total carbon content in the range of 80.0 to 90.0% by mass, preferably 85.0 to 90.0% by mass, more preferably 86.0 to 90.0% by mass, most preferably 87.0 to 90.0% by mass, a total amount of hydrogen in the range of 8.0 to 15.0% by mass, preferably 8.0 to 11.0% by mass, more preferably 8.5 to 10.5% by mass, most preferably 9.0 to 10.0% by mass, and a C / H atomic ratio in the range of 0.60 to 1, preferably 0.65 to 1.0, more preferably 0.70 to 0.90, most preferably 0.70 to 0.85, where the weight percent is based on the total weight of the rubber-derived pyrolysis oil excluding moisture and ash. The total carbon and total hydrogen are measured according to ASTM D5291C-21. The C / H atomic ratio is calculated from the total carbon and total hydrogen. The moisture can be measured according to ASTM D4928-12R18 and the ash can be measured according to ASTM D2415-20 (at 550° C.).
[0072] According to the present invention, the rubber-derived pyrolysis oil can have a total nitrogen content of at least 0.01% by weight, for example at least 0.02% by weight, where the weight percentage is based on the total weight of the rubber-derived pyrolysis oil excluding moisture and ash. The moisture content can be measured according to ASTM D4928-12R18, and the ash content can be measured according to ASTM D2415-20 (at 550°C). The rubber-derived pyrolysis oil can have a total nitrogen content of up to 1.00% by weight, for example up to 0.90% by weight, or up to 0.80% by weight, or up to 0.70% by weight, or up to 0.65% by weight, where the weight percentage is based on the total weight of the rubber-derived pyrolysis oil excluding moisture and ash. A person skilled in the art will understand that any range between any of the explicitly disclosed lower and upper limits is disclosed herein. Thus, the rubber-derived pyrolysis oil may have a total nitrogen content in the range of 0.01 to 1.00 mass%, for example, 0.01 to 0.80 mass%, or 0.01 to 0.65 mass%, where the mass% is based on the total mass of the rubber-derived pyrolysis oil excluding moisture and ash. The total nitrogen content is measured according to ASTM D5291C-21.
[0073] According to the present invention, the rubber-derived pyrolysis oil can have a total sulfur content of up to 1.35% by mass, for example up to 1.30% by mass, or up to 1.25% by mass, or up to 1.20% by mass, or up to 1.15% by mass, or up to 1.10% by mass, where the mass percentages are based on the total mass of the rubber-derived pyrolysis oil excluding moisture and ash. Moisture can be measured according to ASTM D4928-12R18, and ash can be measured according to ASTM D2415-20 (at 550° C.). Total sulfur is measured according to ASTM D5291C-21.
[0074] Rubber-derived pyrolysis oil is a total nitrogen content of at most 1.00% by weight, preferably at most 0.80% by weight, more preferably at most 0.65% by weight, and a total amount of sulfur of at most 1.35% by weight, preferably at most 1.25% by weight, more preferably at most 1.20% by weight, where the weight percent is based on the total weight of the rubber-derived pyrolysis oil excluding moisture and ash. Total nitrogen and total sulfur are measured according to ASTM D5291C-21. Moisture can be measured according to ASTM D4928-12R18 and ash can be measured according to ASTM D2415-20 (at 550° C.).
[0075] According to the present invention, the rubber-derived pyrolysis oil is a total carbon content in the range of 80.0 to 90.0% by mass, preferably 85.0 to 90.0% by mass, more preferably 86.0 to 90.0% by mass, most preferably 87.0 to 90.0% by mass, a total amount of hydrogen in the range of 8.0 to 15.0% by mass, preferably 8.0 to 11.0% by mass, more preferably 8.5 to 10.5% by mass, most preferably 9.0 to 10.0% by mass, a C / H atomic ratio in the range of 0.60 to 1.0, preferably 0.65 to 1.0, more preferably 0.70 to 0.90, most preferably 0.70 to 0.85, a total nitrogen content of at most 1.00% by weight, preferably at most 0.80% by weight, more preferably at most 0.65% by weight, and a total amount of sulfur of at most 1.35% by weight, preferably at most 1.25% by weight, more preferably at most 1.20% by weight, where the weight percent is based on the total weight of the rubber-derived pyrolysis oil excluding moisture and ash. The total carbon, hydrogen, nitrogen and sulfur are measured according to ASTM D5291C-21. The C / H atomic ratio is calculated from the total carbon and hydrogen. The moisture can be measured according to ASTM D4928-12R18 and the ash can be measured according to ASTM D2415-20 (at 550° C.).
[0076] According to the present invention, the rubber-derived pyrolysis oil may have an ash content of less than 0.04 mass %, for example, less than 0.03 mass %, or less than 0.02 mass %, or less than 0.01 mass %, where mass % is based on the total mass of the rubber-derived pyrolysis oil. The ash content is measured according to ASTM D2415-20 (at 550° C.).
[0077] The rubber-derived pyrolysis oil may have a sieve residue of 250 mg / kg or less, for example 230 mg / kg or less, based on the total weight of the rubber-derived pyrolysis oil. The sieve residue is measured according to ASTM D4870-18 (25 μm mesh size).
[0078] According to the present invention, the TPO can have a total carbon content of at least 85.0 wt%, e.g., at least 85.5 wt%, or at least 86.0 wt%, or at least 86.5 wt%, or at least 87.0 wt%, or at least 87.5 wt%, where the wt% is based on the total weight of the TPO excluding moisture and ash. The moisture can be measured according to ASTM D4928-12R18, and the ash can be measured according to ASTM D2415-20 (at 550°C). The TPO can have a total carbon content of 90.0 wt% or less, e.g., 89.5 wt% or less, or 89.0 wt% or less, where the wt% is based on the total weight of the TPO excluding moisture and ash. One of ordinary skill in the art would understand that any range between any of the explicitly disclosed lower and upper limits is disclosed herein. Thus, the TPO may have a total carbon content ranging from 85.0 to 90.0 mass %, preferably 86.0 to 90.0 mass %, more preferably 87.0 to 90.0 mass %, where mass % is based on the total mass of the TPO excluding moisture and ash. The total carbon content is measured according to ASTM D5291C-21.
[0079] According to the present invention, the TPO can have a total hydrogen content of at least 8.0 wt%, for example at least 8.5 wt%, or at least 9.0 wt%, or at least 9.5 wt%, where the wt% is based on the total weight of the TPO excluding moisture and ash. The moisture can be measured according to ASTM D4928-12R18, and the ash can be measured according to ASTM D2415-20 (at 550°C). The TPO can have a total hydrogen content of 11.0 wt% or less, for example, 10.5 wt% or less, or 10.0 wt% or less, where the wt% is based on the total weight of the TPO excluding moisture and ash. One of ordinary skill in the art will understand that any range between any of the explicitly disclosed lower and upper limits is disclosed herein. Thus, the TPO may have a total hydrogen content ranging from 8.0 to 11.0 wt%, preferably 8.5 to 10.5 wt%, more preferably 9.0 to 10.0 wt%, where the wt% is based on the total weight of the TPO excluding moisture and ash. The total hydrogen content is measured according to ASTM D5291C-21.
[0080] According to the present invention, the TPO can have a C / H atomic ratio of at least 0.65, such as at least 0.70, or at least 0.75. The TPO can have a C / H atomic ratio of 1.0 or less, such as 0.95 or less, or 0.90 or less, or 0.85 or less, or 0.80 or less. A person skilled in the art will understand that any range between any of the explicitly disclosed lower and upper limits is disclosed herein. Thus, the TPO can have a C / H atomic ratio ranging from 0.65 to 1.0, preferably 0.70 to 0.90, more preferably 0.70 to 0.85. The C / H atomic ratio is calculated from the total carbon and total hydrogen determined as described above according to ASTM D5291C-21.
[0081] TPO is a total carbon content ranging from 85.0 to 90.0% by mass, preferably from 86.0 to 90.0% by mass, more preferably from 87.0 to 90.0% by mass, a total amount of hydrogen ranging from 8.0 to 11.0% by mass, preferably from 8.5 to 10.5% by mass, more preferably from 9.0 to 10.0% by mass, and a C / H atomic ratio in the range of 0.65 to 1.0, preferably 0.70 to 0.90, more preferably 0.70 to 0.85, where the weight percent is based on the total weight of the TPO excluding moisture and ash. Moisture can be measured according to ASTM D4928-12R18 and ash can be measured according to ASTM D2415-20 (at 550° C.). Total carbon and total hydrogen are measured according to ASTM D5291C-21. The C / H atomic ratio is calculated from the total carbon and total hydrogen.
[0082] According to the present invention, the TPO can have a total nitrogen content of at least 0.40 wt%, e.g., at least 0.45 wt%, or at least 0.50 wt%, where the wt% is based on the total weight of the TPO excluding moisture and ash. The moisture can be measured according to ASTM D4928-12R18, and the ash can be measured according to ASTM D2415-20 (at 550°C). The TPO can have a total nitrogen content of 0.65 wt% or less, e.g., 0.60 wt% or less, or 0.55 wt% or less, where the wt% is based on the total weight of the TPO excluding moisture and ash. One of ordinary skill in the art will understand that any range between any of the explicitly disclosed lower and upper limits is disclosed herein. Thus, the TPO may have a total nitrogen content ranging from 0.40 to 0.65 wt%, preferably 0.45 to 0.65 wt%, more preferably 0.45 to 0.60 wt%, where the wt% is based on the total weight of the TPO excluding moisture and ash. The total nitrogen content is measured according to ASTM D5291C-21.
[0083] According to the present invention, the TPO can have a total sulfur content of up to 1.35 wt%, for example up to 1.30 wt%, or up to 1.25 wt%, or up to 1.20 wt%, or up to 1.15 wt%, or up to 1.10 wt%, where the wt% is based on the total weight of the TPO excluding moisture and ash. Moisture can be measured according to ASTM D4928-12R18, and ash can be measured according to ASTM D2415-20 (at 550°C). Total sulfur is measured according to ASTM D5291C-21.
[0084] TPO is a total nitrogen content of 0.40 to 0.65% by weight, preferably 0.45 to 0.65% by weight, more preferably 0.45 to 0.60% by weight, and a total amount of sulfur of at most 1.35% by weight, preferably at most 1.25% by weight, more preferably at most 1.20% by weight, where the weight percent is based on the total weight of the TPO excluding moisture and ash. Moisture can be measured according to ASTM D4928-12R18, and ash can be measured according to ASTM D2415-20 (at 550° C.). Total nitrogen and total sulfur are measured according to ASTM D5291C-21.
[0085] According to the present invention, the TPO is a total carbon content ranging from 85.0 to 90.0% by mass, preferably from 86.0 to 90.0% by mass, more preferably from 87.0 to 90.0% by mass, a total amount of hydrogen ranging from 8.0 to 11.0% by mass, preferably from 8.5 to 10.5% by mass, more preferably from 9.0 to 10.0% by mass, a C / H atomic ratio in the range of 0.65 to 1.0, preferably 0.70 to 0.90, more preferably 0.70 to 0.85, a total nitrogen content of 0.40 to 0.65% by weight, preferably 0.45 to 0.65% by weight, more preferably 0.45 to 0.60% by weight, and a total amount of sulfur of at most 1.35% by weight, preferably at most 1.25% by weight, more preferably from 0.90 to 1.20% by weight, where the weight percent is based on the total weight of the TPO excluding moisture and ash. Moisture can be measured according to ASTM D4928-12R18 and ash can be measured according to ASTM D2415-20 (at 550° C.). Total carbon, total hydrogen, total nitrogen and total sulfur are measured according to ASTM D5291C-21. The C / H atomic ratio is calculated from the total carbon and total hydrogen.
[0086] According to the present invention, the TPO can have an ash content of less than 0.04 wt%, e.g., less than 0.03 wt%, or less than 0.02 wt%, or less than 0.01 wt%, where wt% is based on the total weight of the TPO. Ash content is measured according to ASTM D2415-20 (at 550° C.).
[0087] The TPO may have a sieve residue of 250 mg / kg or less, such as 230 mg / kg or less, based on the total weight of the TPO, measured according to ASTM D4870-18 (25 μm mesh size).
[0088] According to the present invention, the carbon black feedstock may further comprise a conventional carbon black feedstock, in particular a conventional carbon black feedstock used in a gas black process. The conventional carbon black feedstock may comprise a coal tar distillate, a residual oil produced during catalytic cracking of petroleum fractions, a residual oil produced during olefins production by cracking naphtha or gas oil, or a mixture of any combination thereof, preferably a coal tar distillate.
[0089] The carbon black feedstock of the present invention can comprise up to 90% by weight, for example up to 85% by weight, or up to 80% by weight, or up to 75% by weight, or up to 70% by weight, or up to 65% by weight, or up to 60% by weight, or up to 55% by weight, or up to 50% by weight, or up to 45% by weight, or up to 40% by weight, or up to 35% by weight, or up to 30% by weight, or up to 25% by weight, or up to 20% by weight, or up to 15% by weight, or up to 10% by weight, or up to 5% by weight of conventional carbon black feedstock, based on the total weight of the carbon black feedstock. Thus, the carbon black feedstock of the present invention can comprise up to 70% by weight, preferably up to 50% by weight, more preferably up to 30% by weight, and most preferably up to 10% by weight of conventional carbon black feedstock, based on the total weight of the carbon black feedstock.
[0090] According to the present invention, the carbon black feedstock may comprise at least 5% by weight, for example at least 10% by weight, or at least 15% by weight, or at least 20% by weight, or at least 25% by weight, or at least 30% by weight, or at least 35% by weight, or at least 40% by weight, or at least 45% by weight, or at least 50% by weight, or at least 55% by weight, or at least 60% by weight, or at least 65% by weight, or at least 70% by weight, or at least 75% by weight, or at least 80% by weight, or at least 85% by weight, or at least 90% by weight, or at least 95% by weight, or at least 99% by weight of rubber-derived pyrolysis oil, based on the total weight of the carbon black feedstock. Thus, the carbon black feedstock of the present invention may comprise at least 10% by weight, preferably at least 30% by weight, more preferably at least 50% by weight, even more preferably at least 70% by weight, and most preferably at least 90% by weight of rubber-derived pyrolysis oil, based on the total weight of the carbon black feedstock. The carbon black feedstock of the present invention may consist of rubber-derived pyrolysis oil.
[0091] The present invention further relates to a carbon black obtained by the above-mentioned method of the present invention. The carbon black of the present invention obtained by the method of the present invention can have an oil absorption (OAN) of 100 mL / 100 g or more, for example, 105 mL / 100 g or more, or 110 mL / 100 g or more, or 115 mL / 100 g or more. Preferably, the carbon black of the present invention can have an oil absorption (OAN) of 110 mL / 100 g or more, more preferably 115 mL / 100 g or more. The carbon black of the present invention can have an oil absorption (OAN) of 180 mL / 100 g or less, for example, 175 mL / 100 g or less, or 170 mL / 100 g or less, or 165 mL / 100 g or less, or 160 mL / 100 g or less. The carbon black according to the present invention can have an OAN in the range between any of the recited lower and upper limits. Therefore, the carbon black of the present invention can have an oil absorption (OAN) in the range of 110 mL / 100 g to 180 mL / 100 g, preferably 110 mL / 100 g to 170 mL / 100 g, more preferably 110 mL / 100 g to 165 mL / 100 g, and even more preferably 115 mL / 100 g to 165 mL / 100 g. OAN is measured according to ASTM D2414-21.
[0092] The carbon black of the present invention may have a volatile content of 6% or more, for example 7% or more. The carbon black of the present invention may have a volatile content of 12% or less, for example 11% or less, or 10% or less. The carbon black of the present invention may have a volatile content in the range between any of the recited lower and upper limits. Thus, the carbon black of the present invention may have a volatile content in the range of 6-12%, preferably 6-10%, more preferably 7-10%. The volatile content (at 950°C) is measured according to DIN 53552:1977-09. The volatile content refers to the carbon black of the present invention that has not been oxidized or functionalized after production. The process of the present invention may provide carbon black with a higher volatile content than the gas black process using conventional carbon black raw materials. A high content of volatile content, i.e. a high concentration of surface oxides, may reduce the vulcanization rate and improve the flow properties of the ink. Furthermore, the gloss and blackness of lacquers and coatings containing carbon black with a higher volatile content may be increased. Carbon blacks can be post-treated by oxidation to modify their color properties. The method of the present invention allows for avoidance of such post-treatment.
[0093] The carbon black of the present invention has a viscosity of 70 m 2 / g or more, e.g. 80m 2 / g or more, or 90m 2 The carbon black may have an STSA of 300 m 2 / g or less, e.g. 290m 2 / g or less, or 270m 2 / g or less, or 250m 2 The carbon black according to the present invention can have an STSA ranging between any of the recited lower and upper limits. Thus, the carbon black can have an STSA ranging between 70 and 300 m 2 / g, preferably 70 to 270 m 2 / g, more preferably 80 to 250m 2The polymer may have an STSA in the range of 1 / g. STSA is measured in accordance with ASTM D6556-19a.
[0094] The carbon black of the present invention has a viscosity of 80 m 2 / g or more, e.g. 90m 2 / g or more, or 95m 2 The carbon black may have a BET of 350m / g or more. 2 / g or less, e.g. 320m 2 / g or less, or 300m 2 The carbon black according to the present invention can have a BET ranging between any of the recited lower and upper limits. Thus, the carbon black can have a BET ranging between 80 and 350 m / g or less. 2 / g, preferably 80 to 320 m 2 / g, more preferably 90 to 300m 2 The STSA may have a BET in the range of 1 / g. The STSA is measured according to ASTM D6556-19a.
[0095] The carbon black of the present invention can have a color intensity of 30% or more, for example 40% or more, or 50% or more. The carbon black of the present invention can have a color intensity of 250% or less, for example 230% or less, or 200% or less, or 160% or less. The carbon black of the present invention can have a color intensity in the range between any of the recited lower and upper limits. Thus, the carbon black can have a color intensity in the range of 30 to 250%, preferably 40 to 200%, more preferably 50 to 160%. The color intensity is measured according to ASTM D3265-21.
[0096] The carbon black of the present invention may have a pMC (percent of modern carbon) of 1% or more, for example 2% or more, or 3% or more, or 4% or more, or 5% or more, or 6% or more, or 7% or more, or 8% or more, or 9% or more, or 10% or more, or 12% or more, or 13% or more, or 14% or more, or 15% or more. The carbon black of the present invention may have a pMC (percent of modern carbon) of 95% or less, for example 90% or less, or 80% or less, or 70% or less, or 60% or less, or 55% or less, or 50% or less, or 45% or less. The carbon black according to the present invention may have a pMC in the range between any of the lower and upper limits recited. Thus, the carbon black may have a pMC in the range of 1 to 65%, preferably 5 to 60%, more preferably 10 to 60%, and most preferably 15 to 55%. The pMC is measured according to the ASTM D6866-20B method (AMS). For each sample, 14 C / 13 The C ratio is calculated and compared to measurements made with an oxalic acid II standard (NIST-4990C). The measured values (pMC) are corrected by d13C measured using an isotope ratio mass spectrometer (IRMS).
[0097] According to the present invention, the carbon black can be oxidized. In this specification, the term "oxidized" means that the carbon black has been subjected to an oxidation process and thus contains oxygen-containing functional groups. Thus, oxidized carbon black, unlike non-oxidized carbon black, generally has a significant oxygen content and has oxygen-containing functional groups, examples of which include, but are not limited to, quinone, carboxy, phenol, lactol, lactone, anhydride and ketone groups. For example, the oxidized carbon black can have an oxygen content of 0.5% or more, such as 1% or more, or 2% or more, by weight, based on the total weight of the oxidized carbon black material. Typically, the oxygen content does not exceed 20% by weight, based on the total weight of the oxidized carbon black material. For example, the oxidized carbon black can contain 0.5% to 20% by weight, 1% to 15% by weight, 2% to 10% by weight, or 2% to 5% by weight of oxygen, based on the total weight of the oxidized carbon black material.
[0098] Oxidized carbon black can be prepared by various methods known in the art, such as those disclosed in, for example, U.S. Patent Nos. 6,120,594 and 6,471,933. Suitable methods include the oxidation of the carbon black material with oxidizing agents such as peroxides, such as hydrogen peroxide, persulfates, such as sodium persulfate and potassium persulfate, hypohalites, such as sodium hypochlorite, ozone or oxygen gas, permanganates, transition metal-containing oxidizing agents, such as osmium tetroxide, chromium oxide, ammonium cerium nitrate, or oxidizing acids, such as nitric acid or perchloric acid, as well as mixtures or combinations thereof.
[0099] According to the present invention, the carbon black can be further functionalized. The carbon black can be functionalized by treatment with a functionalizing agent. The functionalized carbon black can be obtained, for example, by treating the oxidized carbon black with a sulfur-containing primary or secondary amine or a salt thereof, as described in WO 2021 / 001156 A1. Thus, this treatment results in a chemical change of the oxidized carbon black, with the sulfur-containing amine imparting functional groups from the treating agent, such as sulfur-containing moieties and / or amine groups, to the oxidized carbon black.
[0100] The present invention further relates to the use of the carbon black of the present invention as a reinforcing filler or additive, a UV stabilizer, a conductive carbon black or pigment, preferably as a pigment.
[0101] Furthermore, the present invention relates to the use of the inventive carbon black in rubber and rubber mixtures, plastics, inks, such as printing inks, inkjet inks or other inks, toners, lacquers, coatings, paper, adhesives or in battery or black matrix applications, preferably in inks, such as printing inks, inkjet inks or other inks, toners, lacquers or coatings, preferably in inks, lacquers or coatings.
[0102] The present invention further relates to a composition comprising the carbon black of the present invention. The composition of the present invention can be an ink composition, a coating composition or a lacquer composition.
[0103] The composition of the present invention may further comprise a polymer component. The polymer component may comprise a thermoplastic polymer, a duroplastic or a thermosetting polymer, as well as mixtures or combinations thereof. For example, the polymer components that can be used in the composition of the present invention include epoxies, acrylics, urethanes, polyesters, polycarbonates, polysulfones, polyimides, polyethers, such as polyethersulfones, polyolefins, such as low-, medium- and high-density polyethylenes, ethylene-propylene copolymers, either random or block structure, polypropylene maleic anhydride, polystyrene, styrene-acrylonitrile copolymers, acrylonitrile-butadiene-styrene copolymers, ethylene-vinyl acetate, ethylene-acrylic acid copolymers, vinyl chloride-polypropylene copolymers, polyisobutylene, polybutadiene, crosslinked polyethylenes that have been subjected to chemical, thermal, UV or electron beam (EB) crosslinking, polyphenylene sulfide, polyetheretherketones, polyetherimides, polyarylsulfones, polypropylene oxide modified polyethersulfones, and mixtures or combinations of any of the foregoing.
[0104] The composition according to the invention may optionally further comprise water and / or one or more organic solvents. For example, the water and / or organic solvent may serve as a dissolving or dispersing medium for the polymeric components and the carbon black of the invention. The composition according to the invention may be a liquid composition, such as, for example, an aqueous or organic dispersion. The organic solvent may comprise an alcohol, a ketone, an ester, an aliphatic or aromatic hydrocarbon, or a mixture thereof. The composition according to the invention may be a powder composition.
[0105] The composition according to the present invention may contain 0.1 to 30% by weight, preferably 0.5 to 20% by weight, more preferably 1 to 15% by weight of the carbon black of the present invention, based on the total weight of the composition.
[0106] The present invention further relates to the use of the compositions of the present invention for printing and coating applications.
[0107] The present invention further relates to articles prepared from the compositions of the present invention. The articles of the present invention may be coated or pigmented or printed articles. EXAMPLES
[0108] The invention is further illustrated by the following examples in which all parts and percentages referred to are by weight unless otherwise indicated.
[0109] Carbon Black Manufacturing Carbon black is produced by the gas black process as described above using a conventional gas black reactor as shown in H. Felch, "Pigments", 1st edition, Kurt R. Vinzenz Publishers, Hannover (1995), p. 33. A procedure similar to that described in Example 1 of US Pat. No. 3,978,019 was used, except that rubber-derived pyrolysis oil was used instead of Russoel. ThermoTireOil RR (Pyram Innovations, Germany) was used as rubber-derived pyrolysis oil. ThermoTireOil RR was subjected to fractional distillation. The fraction of the distilled ThermoTireOil RR having a flash point of at least 65°C was used. The flash point was measured according to ASTM D93B.
[0110] The properties of the carbon black prepared by the gas black process using rubber-derived pyrolysis oil as the carbon black raw material were measured and are listed in Table 1.
[0111] [Table 1]
[0112] Water-based and solvent-based coating compositions were prepared using the carbon black of Example 1, as well as the following commercially available gas blacks obtained using conventional raw materials: Printex® U: 115mL / 100g OAN, 5% volatiles, and 92m 2 Gas black with a BET of 1.0 g / g (Orion Engineered Carbons) Color Black S160: 128mL / 100g OAN, 5% volatiles, and 180m 2 Gas black with a BET of 1.0 g / g (Orion Engineered Carbons)
[0113] Preparation of Aqueous Coating Compositions ("Reference Aqueous Coating Systems") (a) Preparation of aqueous dispersions of each carbon black An aqueous dispersion of each carbon black was prepared as follows in Table 2.
[0114] [Table 2]
[0115] A Skandex dispersion beaker (180 mL, diameter 5.3 cm, height 12.5 cm) was charged with TEGO® Dispers 760W and deionized water and stirred with a spatula. TEGO® Foamex 830 was added and the mixture was stirred with a spatula. Each carbon black was added and the mixture was stirred with a spatula until the carbon black was completely wetted. Dispersions were then carried out for 5 minutes at 4000 rpm using a Pendraulik LR34 dissolver with a 40 mm diameter dispersion disk. The pH of the dispersion was measured. If the pH of the dispersion was below the required range of 8.5-9.2, the pH was adjusted with DMEA. Dispersions were carried out for 60 minutes using a Skandex disperser DAS200, impacting 540 g of chromanite steel beads with a diameter of 3 mm at level 2. The steel beads were then filtered off and the pH of the dispersion was measured. If the pH of the dispersion was below the required range of 8.2-8.7, the pH was adjusted by using DMEA (50 wt % in water).
[0116] (b) Preparation of Reference Lacquer A A benchmark lacquer A was prepared as follows in Table 3.
[0117] [Table 3]
[0118] ALBERDINGK® U9800 was added to the container and stirred with a Pendraulik LR34 dissolver. Butyl glycol, BYK®-024, TEGO® WET280, DMEA and deionized water were premixed and added to ALBERDINGK® U9800. The mixture was dispersed at 1000 rpm with a 40 mm diameter dispersion disk. The mixture was then homogenized at 1500 rpm for 5 minutes. After preparation of the reference lacquer, the reference lacquer was left to stand overnight.
[0119] The quality of reference lacquer A was controlled by applying it onto a glass plate (130 x 90 x 1 mm) and stretching it wet and with uniform tension and pressure using a film stretching bar with a slot height of 200 μm. Care was taken to ensure that no air bubbles were present in the stripe of reference lacquer A. The film stretching bar was placed over the stripe of reference lacquer A and stretched uniformly across the plate. A stretch of approximately 10 cm in length and 6 cm in width was produced.
[0120] After the above stretching procedure, the wet coating film on the glass plate was flashed off at room temperature (20° C.) for 15 minutes, and then the coated glass plate was dried at 60° C. for 15 minutes.
[0121] The coatings prepared from the reference lacquer A were checked for defects such as craters, spots and irregularities. If there was a significant number of defects, the reference lacquer was freshly prepared for use in the formulation of the coating composition described below.
[0122] (c) Preparation of the aqueous coating composition Aqueous coating compositions were prepared from benchmark lacquer A and aqueous dispersions of each carbon black (Table 2) according to the formulations below in Table 4.
[0123] [Table 4]
[0124] The aqueous dispersions prepared from each carbon black and the reference lacquer A were weighed into an 80 mL beaker in the amounts described above and thoroughly homogenized with a spatula until homogenous to obtain the corresponding aqueous coating compositions.
[0125] Preparation of Solvent-Based Coating Compositions (a) Preparation of solvent-based dispersions from each carbon black A solvent-based dispersion of each carbon black was prepared as follows in Table 5.
[0126] [Table 5]
[0127] Setal® F310SN and Shellsol® A were placed in a Skandex dispersion beaker (180 mL, diameter 5.3 cm, height 12.5 cm) and thoroughly homogenized with a spatula. Each carbon black was added and the mixture was stirred with a spatula until the carbon black was completely wetted. Dispersion was then carried out for 5 minutes at 4000 rpm using a Pendraulik LR34 dissolver with a 40 mm diameter dispersion disk. Dispersion was carried out for 60 minutes using a Skandex disperser DAS200 with 550 g of 2 mm diameter steel beads impacting at level 2. The steel beads were then filtered off.
[0128] (b) Preparation of Solvent-Based Coating Compositions From the solvent-based dispersion thus obtained, a solvent-based coating composition was prepared according to the following formulation (see Table 6).
[0129] [Table 6]
[0130] The above components were weighed into a 180 mL beaker in the amounts indicated and thoroughly homogenized with a spatula for 10 minutes to obtain the corresponding solvent-based coating composition.
[0131] Preparation of films from the coating compositions Films were prepared from the aqueous and from the solvent-based coating compositions as follows.
[0132] Each coating composition was applied onto a glass plate (130×90×1 mm) and stretched wet and with uniform tension and pressure using a film stretching bar with a slot height of 200 μm (for aqueous coating compositions) or 100 μm (for solvent-based coating compositions). Care was taken to ensure that no air bubbles were present in the stripe of coating composition. The film stretching bar was positioned over the stripe of coating composition and stretched uniformly across the plate. A stretch approximately 10 cm long and 6 cm wide was produced.
[0133] After the above stretching procedure, the resulting wet coating film on the glass plate was flashed off at room temperature (20° C.) for 15 minutes and then the coated glass plate was dried at 130° C. for 15 minutes (for solvent-based coating compositions) or flashed off at room temperature (20° C.) for 15 minutes and then dried at 60° C. for 15 minutes (for water-based coating compositions).
[0134] The coating compositions thus prepared were analyzed for their pigmentation properties.
[0135] The color properties of the films thus prepared from the water-based and solvent-based coating compositions were measured using a Pausch Color35 spectrophotometer (45° / 0° spectrophotometer) and BCSWIN software. Measurements were taken through glass after calibration with a white calibration tile and a black hollow body. The spectrophotometer averaged over five individual measurements for each sample.
[0136] Hue-independent black value M Y and the hue-dependent black value, Mc, was calculated from the measured derived tristimulus (XYZ) data as follows:
[0137] Hue-independent black value M Y was calculated from the tristimulus component Y of the measured value (illuminant D65 / 10°) according to Equation 1.
number
[0138] Then, the hue-dependent black value was calculated according to Equation 2.
number
[0139] In the formula, X n / Z n / Y n (DIN 6147) are the tristimulus values of the coordinate origin based on the illuminant and observer (DIN 5033 / 7 parts / illuminant D65 / 10°) with the following values: X n =94.81 Z n =107.34 Y n =100.0
[0140] The absolute hue contribution dM is the sum of the black values Mc and M Y was calculated according to Equation 3.
number
[0141] Haze and gloss 20° were measured according to DIN EN ISO2813:2015.
[0142] To measure relative color intensity, coating compositions containing white pigment (TiO2) and aqueous or solvent-based dispersions of each carbon black were prepared according to the following procedure.
[0143] Preparation of the Aqueous Coating Composition (a) Preparation of reference lacquer B A benchmark lacquer B was prepared as follows in Table 7.
[0144] [Table 7]
[0145] A dispersion beaker (850 mL) was charged with TEGO® Dispers 760W and BYK®-024 and thoroughly homogenized with a spatula. 5 g of butyl glycol and DMEA were added and the mixture was thoroughly homogenized with a spatula. Kronos® 2064 was added and the mixture was stirred with a spatula until the Kronos® 2064 was completely wetted. Dispersion was then carried out with a Pendraulik LR34 dissolver using a 60 mm diameter dispersion disk at 4000 rpm for 5 min. The dissolver was covered with aluminum foil to prevent evaporation of the solvent. The beaker was then checked with a spatula for adhesion of pigment agglomerates. The dispersion was cooled to a maximum of 30°C.
[0146] ALBERDINGK® U9800 was added to the vessel. 33.7 g of butyl glycol and deionized water were premixed and added to ALBERDINGK® U9800, and the mixture was dispersed at 1000 rpm using a dispersing disk with a diameter of 60 mm. The mixture was then homogenized for 5 minutes at 1000 rpm. The mixture thus prepared was added to a mixture containing TEGO® Dispers 760W, BYK®-024, butyl glycol, DMEA and Kronos® 2064, and the mixture was dispersed at 1000 rpm using a dispersing disk with a diameter of 60 mm. The mixture was then homogenized for 5 minutes at 2000 rpm. The pH of the dispersion was measured. If the pH of the dispersion was below the required range of 8.5-9.0, the pH was adjusted using DMEA. After preparation of the reference lacquer B, the reference lacquer B was left to stand overnight.
[0147] The quality of the reference white lacquer B was controlled by applying it onto a glass plate (130 x 90 x 1 mm) and stretching it wet and with uniform tension and pressure using a film stretching bar with a slot height of 200 μm. Care was taken to ensure that no air bubbles were present in the stripe of reference lacquer B. The film stretching bar was placed on the stripe of reference lacquer B and stretched uniformly across the plate. A stretch of approximately 10 cm in length and 6 cm in width was produced.
[0148] After the above stretching procedure, the wet coating film on the glass plate was flashed off at room temperature (20° C.) for 15 minutes, and then the coated glass plate was dried at 60° C. for 15 minutes.
[0149] The coatings prepared from the reference lacquer B were checked for defects such as craters, spots and irregularities. If there was a significant number of defects, the reference lacquer was freshly prepared for use in the formulation of the coating composition described below.
[0150] (b) Preparation of the aqueous coating composition Aqueous coating compositions were prepared from benchmark lacquer B and the aqueous dispersions of Table 2 according to the following formulations in Table 8.
[0151] [Table 8]
[0152] The aqueous dispersions prepared from each carbon black and the reference lacquer B were weighed into a beaker in the amounts mentioned above and thoroughly homogenized with an enamel paint brush.The mixture was then homogenized for 2 minutes at 2000 rpm using a speed mixer.
[0153] Preparation of Solvent-Based Coating Compositions (a) Preparation of reference lacquer C A benchmark lacquer C was prepared as follows in Table 9.
[0154] [Table 9]
[0155] A dispersion beaker (180 mL) was charged with 60.0 g of Setal® F310SN. Kronos® 2301 was added and the mixture was thoroughly homogenized with a spatula until the Kronos 2310 was completely wetted. Dispersion was then carried out with a Pendraulik LR34 dissolver using a 40 mm diameter dispersion disk at 4000 rpm for 5 min. The beaker was checked with a spatula for adhesion of pigment agglomerates. Dispersion was further carried out with a Pendraulik LR34 dissolver using a 40 mm diameter dispersion disk at 4000 rpm for 10 min. The dissolver was covered with aluminum foil to prevent evaporation of the solvent. The dispersion was cooled to a maximum of 30°C.
[0156] 7.35 g of Setal® F310SN, Maprenal® MF800 / 55IB, and xylene were added to the mixture, thoroughly homogenizing with a spatula after each addition, followed by dispersion using a Pendraulik LR34 dissolver with a 40 mm diameter dispersion disk at 1500 rpm for 5 minutes.
[0157] (b) Preparation of Solvent-Based Coating Compositions Solvent-based coating compositions were prepared from the benchmark lacquer C in Table 5 and the solvent-based dispersions according to the following formulations in Table 10.
[0158] [Table 10]
[0159] The aqueous dispersions prepared from each carbon black, and reference lacquer B were weighed into a beaker in the amounts stated above and thoroughly homogenized with a spatula followed by a rubber wiper.
[0160] Preparation of films from the coating compositions Films are prepared from the aqueous and from the solvent-based coating compositions as follows.
[0161] Each coating composition was applied onto a glass plate (130×90×1 mm) and stretched wet and with uniform tension and pressure using a film stretching bar with a slot height of 150 μm. Care was taken to ensure that no air bubbles were present in the stripe of coating composition. The film stretching bar was positioned over the stripe of coating composition and stretched uniformly across the plate. A stretch approximately 10 cm long and 6 cm wide was produced.
[0162] After the above stretching procedure, the resulting wet coating film on the glass plate was flashed off at room temperature (20° C.) for 15 minutes and then the coated glass plate was dried at 130° C. for 15 minutes (for solvent-based coating compositions) or flashed off at room temperature (20° C.) for 15 minutes and then dried at 60° C. for 15 minutes (for water-based coating compositions).
[0163] The coating compositions thus prepared were analyzed for relative color strength, which was measured according to DIN EN ISO787-24:1995-10.
[0164] The results for the tinting properties of the water-based coating compositions containing carbon black are summarized in Table 11, and the results for the solvent-based coating compositions are summarized in Table 12.
[0165] [Table 11]
[0166] [Table 12]
Claims
1. 1. A process for producing carbon black by thermo-oxidative decomposition of a carbon black feedstock, wherein the carbon black feedstock comprises a rubber-derived pyrolysis oil, and the production of carbon black is carried out in a gas black reactor.
2. The method of claim 1 , wherein the rubber-derived pyrolysis oil comprises tire-derived pyrolysis oil (TPO).
3. 3. The method according to claim 1 or 2, wherein the rubber-derived pyrolysis oil comprises tire-derived pyrolysis oil (TPO).
4. Rubber-derived pyrolysis oil, - a total carbon content in the range of 80.0 to 90.0% by mass, - a total amount of hydrogen in the range of 8.0 to 15.0% by weight, and - has a C / H atomic ratio ranging from 0.60 to 1.0, Here, mass % is based on the total mass of the rubber-derived pyrolysis oil excluding moisture and ash, and the total carbon and total hydrogen contents are measured according to ASTM D5291C-21, and / or Rubber-derived pyrolysis oil, - a maximum total amount of nitrogen of 1.00% by weight, and - has a maximum total sulfur content of 1.35% by mass, Here, mass% is based on the total mass of the rubber-derived pyrolysis oil excluding moisture and ash, and the total nitrogen content and the total sulfur content are measured in accordance with ASTM D5291C-21. The method according to any one of claims 1 to 3.
5. Tire-derived pyrolysis oil (TPO) - a total carbon content in the range of 85.0 to 90.0% by mass, - a total amount of hydrogen in the range of 8.0 to 11.0% by weight, and - has a C / H atomic ratio ranging from 0.65 to 1.0, The method according to any one of claims 2 to 4, wherein the mass % is based on the total mass of the TPO excluding moisture and ash, and the total carbon and total hydrogen are measured according to ASTM D5291C-21.
6. 6. The process according to any one of claims 1 to 5, wherein the carbon black feedstock further comprises a conventional carbon black feedstock comprising coal tar distillate, residual oil produced during catalytic cracking of petroleum fractions, residual oil produced during olefins production by cracking naphtha or gas oil, or a mixture of any combination thereof, preferably coal tar distillate.
7. the carbon black feedstock comprises at least 10 wt.%, preferably at least 30 wt.%, more preferably at least 50 wt.%, even more preferably at least 70 wt.%, and most preferably at least 90 wt.%, of rubber-derived pyrolysis oil, based on the total weight of the carbon black feedstock; or The method according to any one of claims 1 to 6, wherein the carbon black raw material comprises rubber-derived pyrolysis oil.
8. vaporizing the carbon black feedstock in a carrier gas stream; combusting the carrier gas stream loaded with the carbon black feedstock in the presence of air in a burner to form carbon black; and The method of any one of claims 1 to 7, comprising terminating carbon black formation.
9. 9. A carbon black obtained by the method according to any one of claims 1 to 8, wherein the carbon black is a gas black.
10. Carbon black is - an oil absorption number (OAN) of 110 mL / 100 g or more, and / or - having a volatile content of 6% or more, 10. The carbon black of claim 9, wherein OAN is measured according to ASTM D2414-21 and volatiles (at 950° C.) is measured according to DIN 53552:1977-09.
11. 11. The carbon black of claim 9 or 10, wherein the carbon black has at least one, more than one, or all of the following: - an OAN in the range of 110 to 180 mL / 100 g, preferably 115 to 165 mL / 100 g, where OAN is measured according to ASTM D2414-21; - a volatile content in the range of 6% to 25%, where the volatile content (at 950 ° C) is determined according to DIN 53552: 1977-09; - 70 to 300 m 2 / g, preferably 70 to 270 m 2 / g, more preferably 80 to 250 m 2 / g, where STSA is measured according to ASTM D6556-19a; - 80 to 350 m 2 / g, preferably 80 to 320 m 2 / g, more preferably 90 to 300 m 2 / g, where BET surface area is measured according to ASTM D6556-19a; a colour strength ranging from 30 to 250%, preferably from 50 to 160%, where the total amount of sulphur is measured according to ASTM D3265-21; - pMC (percent modern carbon) in the range of 1-65%, preferably 5-60%, more preferably 10-60%, even more preferably 15-55%, where pMC is measured according to ASTM D6866-20B method (AMS).
12. Use of the carbon black according to any one of claims 9 to 11 as a reinforcing filler or additive, as a UV stabilizer, as a conductive carbon black or pigment, preferably as a pigment.
13. 12. Use of the carbon black according to any one of claims 9 to 11 in rubber and rubber mixtures, plastics, inks, such as printing inks, inkjet inks or other inks, toners, lacquers, coatings, paper, adhesives or in battery or black matrix applications, preferably in inks, lacquers or coatings.
14. A composition comprising the carbon black according to any one of claims 9 to 11, which is preferably an ink composition, a coating composition or a lacquer composition.
15. 15. An article prepared from the composition of claim 14.